2021
DOI: 10.1186/s12969-021-00563-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Fabry disease in a juvenile idiopathic arthritis cohort

Abstract: Background Fabry disease (FD) is a rare, X-linked, multisystemic lysosomal storage disorder (LSD) that results from a deficiency in the hydrolase alpha-galactosidase A (⍺-GalA). During childhood, classic FD symptomatology is rare. The majority of children may show non-specific symptoms, including in the musculoskeletal system. The prevalence of FD among juvenile idiopathic arthritis (JIA) patients is unknown. Objective This study aimed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…При этом не происходит органического поражения и деструкции суставов, а данные изменения лишь имитируют системные проявления и являются ревматологическими «масками» болезни Фабри [19]. Особенно рекомендовано исключать болезнь Фабри у пациентов с юношеским артритом при явном отсутствии эффекта от проводимой терапии и сохранении болевого синдрома без лабораторных и инструментальных изменений, характерных при данном заболевании [20].…”
Section: Discussionunclassified
“…При этом не происходит органического поражения и деструкции суставов, а данные изменения лишь имитируют системные проявления и являются ревматологическими «масками» болезни Фабри [19]. Особенно рекомендовано исключать болезнь Фабри у пациентов с юношеским артритом при явном отсутствии эффекта от проводимой терапии и сохранении болевого синдрома без лабораторных и инструментальных изменений, характерных при данном заболевании [20].…”
Section: Discussionunclassified
“… 51 A recent study of our group observed a frequency of 1.12% of FD in a cohort of juvenile idiopathic arthritis (JIA) patients. 52 …”
Section: Clinical Manifestations Of Fd By Organ Systemsmentioning
confidence: 99%